2019
DOI: 10.1097/mph.0000000000001373
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Hearing Loss in Patients With Sickle Cell Disease in the United States

Abstract: This study sought to examine if modern medical evaluations including newborn screening and early diagnosis along with better methods of disease control have improved rates of hearing loss in children with sickle cell disease (SCD). Audiometric and medical data for patients with SCD was obtained from the AudGen Database and analyzed for the presence of hearing loss, type of hearing loss, severity of hearing loss, and correlation with comorbid conditions. Children with sickle cell trait (SCT) were used as a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Between 13% and 62% of tested patients are affected by hearing loss, with 6.6% to 13% having a component of sensorineural hearing loss. [50][51][52] FIGURE 3: Functional connectivity matrices per cohort. The intra-network spherical parcellations (on the diagonal) have a strong positive correlation compared with the inter-network spherical parcellations, showing that the functional network architecture is similar between the control (left) and sickle cell disease (SCD) cohort (middle).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 13% and 62% of tested patients are affected by hearing loss, with 6.6% to 13% having a component of sensorineural hearing loss. [50][51][52] FIGURE 3: Functional connectivity matrices per cohort. The intra-network spherical parcellations (on the diagonal) have a strong positive correlation compared with the inter-network spherical parcellations, showing that the functional network architecture is similar between the control (left) and sickle cell disease (SCD) cohort (middle).…”
Section: Discussionmentioning
confidence: 99%
“…We also found decreased connectivity within the auditory network, which is supported by mounting evidence that patients with SCD suffer hearing loss. Between 13% and 62% of tested patients are affected by hearing loss, with 6.6% to 13% having a component of sensorineural hearing loss 50–52 . Hearing loss has been associated with fcMRI changes, 53 and undiagnosed and untreated hearing loss can potentially impact cognitive development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, electronic health records (EHRs) combine encounter records with problem lists of patient diagnoses recorded by clinicians, and studies have demonstrated the accuracy of EHR diagnosis codes for the identification of people living with SCD 7,8 . Similarly, health system databases can identify those with clinical diagnoses of SCD 9 . This critical review is intended to help researchers choose among algorithms in stand‐alone administrative databases lacking clinical or laboratory records to identify individuals, especially children and adolescents, living with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…clinical diagnoses of SCD. 9 This critical review is intended to help researchers choose among algorithms in stand-alone administrative databases lacking clinical or laboratory records to identify individuals, especially children and adolescents, living with SCD.…”
mentioning
confidence: 99%
“…Audiological data analyses were adapted from previous AudGenDB studies . Pure‐tone air‐ and bone‐conduction audiometry and sound‐field testing were used to evaluate hearing outcomes.…”
Section: Methodsmentioning
confidence: 99%